Numerical Analysis On MHD Stagnation-Point Flow Of Casson Fluid And Heat Transfer Over a Stretching Sheet - Ahnantha Rajah, Nagadehvan; Md Shab, Mdm Noorzehan Fazahiyah (Enhanced Knowledge in Sciences and Technology, 2023)
This paper is to study the MHD-stagnation point flow of casson fluid over a stretching sheet.The governing momentum and energy equations are transformed to self-similar nonlinear ODEs through similarity transformations, and then those equations are solved numerically by using shooting method in Maple. If velocity ratio parameter, B and magnetic parameter M increase, then the velocity boundary layer thickness becomes thinner. With the Casson parameter (), the wall skin-friction coefficient’s magnitude decreases.